Pengaruh Komunikasi Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Karyawan CV. Dijawa Abadi Kayu Lama Jepara - Rhaynald Allamsyah; Kis Indriyaningrum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study analyzes the influence of communication, leadership style, and work environment on employee performance at CV Dijawa Abadi Kayu Lama Jepara. In this study, samples were taken by the saturated sample method, which is a sampling technique when all members of the population are used as samples. The results of this study show that communication, leadership style and work environment have a positive and significant effect on the performance of employees in CV Dijawa Abadi Kayu Lama Jepara